Captive Wives or Conjugal Slaves? The Slavery-Marriage Nexus in Northern Uganda Since the Mid-Nineteenth Century. (3rd April 2022) - Seymour, Eleanor; Apio, Eunice; Rossi, Benedetta
ABSTRACT: This article examines transformations in the marriage-slavery nexus in Northern Uganda from the late nineteenth century to the present. By historicizing the forced marriage of abducted girls in the Lord's Resistance Army, the article contributes to explaining why the interpretation of these circumstances has been so disputed in Uganda and internationally. It starts by examining different interpretations of the relationship between Dominic Ongwen and his forced wives. The Ongwen case is then contextualized in the history of female captivity and conjugal violence in Lango and Acholi societies. It is argued that enslavement in the form of wartime captivity was not irreconcilable with marriage in Northern Uganda in the late nineteenth and early twentieth centuries, and that this history influences contemporary Lango and Acholi perceptions of these phenomena.